A landmark-based approach for assessing the reliability of mandibular tooth crowding as a marker of dog domestication. (September 2017) - Ameen, Carly; Hulme-Beaman, Ardern; Evin, Allowen; Germonpré, Mietje; Britton, Kate; Cucchi, Thomas; Larson, Greger; Dobney, Keith
Abstract: Tooth crowding is one of several criteria used to infer the process of domestication in the zooarchaeological record. It has been primarily used to support claims of early animal domestication, perhaps most contentiously in claims for the existence of so-called "proto-domestic" dogs as early as the Middle-Upper Palaeolithic. Tooth crowding studies vary in their methodological approaches, and interpretation of the resulting data is constrained by the limited geographic and temporal scope of reference specimens used to construct an appropriate comparative framework. To address these key problems, we present a standardised landmark-based protocol for the measurement and quantification of mandibular tooth crowding that can be systematically applied in the context of dog domestication research. We then test the assumption that tooth crowding is less frequent in ancient and modern wild wolf populations by examining 750 modern dogs and 205 modern wolves from across the modern geographic range of Canis lupus as well as 66 Late Pleistocene wolves from Alaska. Our results demonstrate that landmark-based metrics provide a reliable approach for recording and analysing tooth crowding. Although it is likely that the relatively low frequency of tooth crowding found in our modern dog dataset (∼6%) in part reflects the 'modern' morphology of domestic breeds, the higher frequency of crowding in both modern (∼18%) and ancient (∼36%) wolves strongly suggests that current assumptions linking tooth crowding with the process of early domestication (at least in dogs) should be critically re-evaluated, and that further investigations into the drivers behind these developmental patterns should be pursued. Highlights: A novel landmark-based protocol to record mandibular tooth crowding is presented. Report high levels of tooth crowding in ancient and modern wolves relative to dogs. LDA suggests that wolves and dogs cannot be separated based on tooth crowding. Discourages use of tooth crowding as a marker of the early domestication process. Further research should explore developmental driving processes of tooth crowding.